Factors Related with Anemia in Pregnant Women in Johan Pahlawan Sub-District, West Aceh District - Susy Sriwahyuni; Fitriani Fitriani; Azwar Azwar (Universitas Teuku Umar, 2020)
Anemia in Pregnant Women is a health problem during pregnancy. Where the state of decreased hemoglobin levels and the number of red blood cells below normal values. Increased need for iron nearly tripled for the needs of mothers and fetuses during pregnancy, anemia in pregnant women has an impact on morbidity and maternal death, the risk of low birth weight, premature birth. Anemia can also be avoided by consuming foods that often contain animal protein and vegetable protein. Iron (Fe) intake, knowledge, and family support have an important role in the incidence of anemia in pregnancy. This type of research is a cross sectional survey. The study was conducted in Johan Pahlawan Sub-district, West Aceh District. The population is all pregnant women trimester II and III of 54 pregnant women. Taking in total sampling, data analysis used Univariate analysis and Bivariate (Chi-Square test). The results of the study obtained a relationship between the knowledge factor with the P-value = 0.001 and the Family Support factor with a P-value = 0.004 with the incidence of anemia in pregnant women. Expected mothers are expected to know the importance of consuming iron (Fe) intake, extensive knowledge about the dangers of anemia during pregnancy and the importance of family support for pregnant women to avoid anemia.